Risk Management Analysis of Construction Projects on Time Performance - Al Matin, Muhammad Ma'ruf; Firdausi, Annisa Azhar; Safarizki, Hendramawat Aski (Science and Technology Research Centre, Universitas PGRI Semarang, 2022)
Project risk is an uncertain situation in a project so that it can lead to consequences that can hinder the achievement of the main project objectives. Risks to the project need to be identified and analyzed in order for the project to run well. The Hidayatul Qur'an Lissa'adah Islamic Boarding School construction project is a self-managed construction project that experienced delays in its implementation time based on the results of observations and preliminary interviews with the development committee. With risk management aims to identify and reduce the risks that occur in the implementation of the Hidayatul Qur'an Lissa'adah Islamic Boarding School construction project so that the project can be completed immediately. Project delays cannot be separated from the existence of several risks that cannot be avoided, but can be minimized by risk management. In this study, identification with the Cochran q-test was carried out on the risks to determine the risks that greatly affect delays in the project, then carried out an analysis of the risks that occurred with the saverity index and then carried out appropriate mitigation actions against these risks, so that the project could be completed immediately. Based on tests and calculations using the Cochran q-test and saverity index. The results obtained through this study are that there are 4 dominant risks in the medium and high categories, namely the risk of incorrect or incomplete design (11.39%), the risk of cash flow congestion (11.39%), the risk of problematic service providers (20.25 %) and the risk of the covid pandemic outbreak (31.64%).